EFFECTIVENESS OF BUSINESS EDUCATION PROGRAMME AND THE DEVELOPMENT OF EMPLOYABILITY SKILLS OF BUSINESS EDUCATION STUDENTS IN PUBLIC UNIVERSITIES IN LAGOS STATE, NIGERIA - Ore, Elizabeth Remilekun (African Journal of Educational Management, 2023)
It is of great importance for the educational system of any country to produce graduates that are self-reliant who are able to fit effectively into the world of work. Thus, the purpose of this paper was to assess the effectiveness of Business Education programme and the development of employability skills of business education students in public universities in Lagos State, Nigeria. Three hypotheses were formulated and tested at the 0.05 level of significance. Descriptive survey research design method was adopted for the study. The population of the study was 350 Business Education students from two public universities in Lagos State who were in 400 level and purposive sampling technique was used to draw the 80 sample size from the population. A four-point Likert rating structured questionnaire titled “Effectiveness of Business Education Programme on Graduates’ Employability Skills” (EBEPGES) was employed to gather data from 80 respondents with a reliability coefficient of 0.85. Least Square Regression test statistics was used to test hypothesis one, while Person’s Product Moment Correlation (PPMC) was used to test hypotheses two and three. Results from the findings revealed that business education curriculum content does not equip students with the required soft skills needed to excel in work environment, the integration of work place job requirement in the curriculum content will enhance the employability skills of Business Education students and that there is statistical negative significant relationship between Business Education instructional methods and students’ employability skills in public Universities in Lagos State. Based on the findings, the study recommended that the work environment and school should be integrated and all the major soft skills required by employers should be included into the curriculum as this will serve as a plus to the students when they eventually graduate to seek for job opportunities.